DEVELOPMENT EXTENSION SERVICE TO MEETING THE REQUIREMENTS OF BUFFALO BREEDERS IN IRAQ - & et al., Al-Taiy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The  aim of this research is to development the effectiveness of extension service  to meeting  the requirements of buffalo breeders in Iraq. The research was concluded in four fields: the first field: Development and adopting an appropriate orientation. It included four axes: Diversifying sources of extension services, comprehensiveness, decentralization, modernization of the work method. Second Field: Organizational Development. It included two axes: strengthening specialized organization (formation of specialized guidance units), capacity development.  Third Field: Service Feasibility Development. It includes five axes: service based on the requirements of breeders and the characteristics of their projects, the quality of the content of the service, the use of modern means of communication, appropriate allocations, follow-up, evaluation, and continuous improvement. Four Field: Provide an appropriate external environment. It includes three axes: an enabling environment. The Implementation of a national program for developing buffalo  in Iraq.